The efficacy and safety of local 5-aminolevulinic acid-based photodynamic therapy in the treatment of cervical high-grade squamous intraepithelial lesion: a single center retrospective observational study - Qian, Jing; Wang, Yahui; Wu, Guihong; Lu, Junlei; Sun, Liping; Xu, Song (Frontiers in Oncology, 2024)
1. Background: Typical treatments for cervical high-grade squamous intraepithelial lesion (HSIL) are invasive procedures. However，these procedures often come with several severe side effects, despite their positive effects on cervical HSIL. 5-aminolevulinic acid photodynamic therapy (ALA-PDT) is a non-invasive treatment that has been successfully used to treat cervical low-grade squamous intraepithelial lesion (LSIL). In this study, we aimed to further investigate the clinical efficacy and safety of ALA-PDT in the treatment of patients with cervical HSIL.: A total of 40 patients aged 20 -41 years with cervical HSIL and high-risk Human Papilloma Virus (HR-HPV) infections were enrolled in this retrospective study from January 2019 to December 2022. Patients were treated with six times of ALA-PDT at intervals of 7-14 days. Three months after the treatment, the efficacy was evaluated through HPV genotyping and cervical cytology examination. If the cytological result was worse than ASC -US, the patient underwent colposcopy-directed biopsy immediately. Otherwise, patients would receive rigorous follow-up observation. 3. Results: Three months after receiving ALA-PDT treatment, 65% (26/40) of cervical HSIL patients at our center showed complete regression (cytological result: normal; HR-HPV: negative). This rate increased to 82.5% (33/40) at the 12-month follow-up. None of the patients experienced disease progression after ALA-PDT therapy. The risk of persistent HR-HPV infection was 32.5% (13/40) at the 3-month follow-up after ALA-PDT. Multivariate analyses identified cervical canal involvement as an independent risk factor for persistent HR-HPV infection at the 3-month follow-up after ALA-PDT treatment. During the treatment of the 40 patients with ALA-PDT, there were no reports of severe adverse reactions. Only a limited number of patients experienced slight discomfort symptoms. 4. Conclusions: ALA-PDT is safe and effective noninvasive therapy for patients with cervical HSIL and HR-HPV infections. It is particularly suitable for young women，who have been confirmed with cervical HSIL and have demand for fertility protection. Three months after ALA-PDT treatment, if a patient still has either ASC-US cervical cytological result and/or HR-HPV infection, rigorous observation is considered safe for her. Cervical canal involvement is an independent risk factor for persistent HR-HPV infection at the 3-month follow-up after ALA-PDT treatment.